Feasibility study for the creation and implementation of a specialization on translation English - Spanish, Spanish - English for modern languages program at ECCI university. (2016)
The following thesis analyze the feasibility of a specialization at ECCI (Escuela Colombiana de Carreras Industriales) University, which is mainly focused in Translation, in order to do it, information is provided about the different types of programs on Translation offered at national and international level, from there, it pays particular attention to the gathered information regarding the possibility of a specialization based exclusively on English-Spanish, Spanish-English Translation, it would highlight and increase the acquired skills in Modern Language Program, observing the strengths and weaknesses of it, while it would offer new perspectives on them; then it describes how this possible specialization would enhance and connect Modern Languages Program with Specialization in Translation.